G622 Which factors affect the medication stability of patients with adhd through the transitional period from paediatric to adult care?. (25th October 2020) - Edmonds, M; Gallagher, R
Abstract : Aims: It is known that adolescents with a diagnosis of attention deficit hyperactivity disorder (ADHD) are particularly vulnerable at the transitional period from paediatric to adult care. The aim of this study is to determine factors which may affect the prescription stability of adolescent patients who live with ADHD. Methods: We conducted a retrospective cohort study investigating 65 adolescents who were receiving prescriptions for ADHD medication. The patients were categorised into two groups, 'stable' and 'unstable', based on prescription changes over a three year period. The groups were then compared based on the medication prescribed, dose of medication, comorbidities, BMI and gender and reasons for prescription changes were noted. Results: The study found a statistically significant correlation between adolescents prescribed Elvanse and prescription changes (OR: 19.63 P≤0.05). Further to this Patients who were receiving an unlicensed dose of Concerta XL were also more likely to have a prescription change (OR: 11.00 P≤0.05). A key finding was the strong association between side effects and instability of prescriptions (OR: 936 P≤0.0001). Conclusion: This study revealed associations between patients prescribed Elvanse and increased changes to their medications. This also applied to those receiving an unlicensed dose of Concerta XL. This study also highlights the common reasons for medication change (table 1 ) in this transitionary period.